GAMBARAN PENGELOLAAN LIMBAH PADAT B3 DI RUMAH SAKIT UMUM DAERAH ADE MUHAMMAD DJOEN SINTANG - Suparti; Supraptono, Bambang; Asmadi (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Pontianak, 2022)
The increasing number of hospitals in Indonesia, the production of medical waste produced is also increasing. Therefore, it is necessary to manage waste in B3 to avoid injury and environmental pollution. B3 waste generated by hospitals can cause disruption of health protection and or risk of pollution to the environment. The existence of good waste management is expected to minimize the impact. This study aims to describe the stages of sorting, storage, transportation, and final processing, at Ade Muhammad Djoen Sintang Regional General Hospital. This type of research uses descriptive observational, data collection is done by means of interviews and observations, then presented in tabular form, and described in narrative form. The results showed that the value of sorting was 50, storage was 35, transportation was 85, temporary storage was 80, and final processing was 175. It is recommended that the waste storage place has a plastic bag color that matches the type of medical waste and non-medical waste, transported every day so that there are no insects. and smells.